Association of volunteer-administered home care with reduced emergency room visits and hospitalization among older adults with chronic conditions: A propensity-score-matched cohort study. (March 2022) - Lai, Francisco Tsz Tsun; Wong, Eliza LY; Tam, Zoe PY; Cheung, Annie WL; Lau, Mun-Cheung; Wu, Chun-Man; Wong, Rex; Ma, Hon-Ming; Yip, Benjamin HK; Yeoh, Eng-Kiong
Abstract: Objectives: The objective of this study was to examine the association of receiving care from a volunteer-administered outreach program with emergency room utilization and hospitalization among older people with chronic conditions in Hong Kong. Methods: Volunteers consisting of retired healthcare professionals, university students, and openly recruited citizens received training to provide home care services to hospital-discharged older Chinese adults aged 65+ with chronic conditions who were identified as high-risk patients of hospital admission and referred by public healthcare providers. Several home visits were made to enhance the patients' self-care capacity. For comparison, a 4:1-propensity score matching based on age, sex, the month of discharge, length of stay for the index episode, and 14 common chronic conditions was conducted to select a comparison group from a territory-wide inpatient database. Poisson regression was used to compare emergency room utilization and the number of hospitalized days. Results: In total, 775 patients were analyzed, including 155 home care recipients and 620 extracted from the inpatient database as a matched comparison with similar baseline characteristics. Regression analysis showed that home care recipients had 21% fewer overall emergency room visits [95% confidence interval (CI): 3%–35%], 22% fewer such visits which led to hospitalization (95% CI: 1%–39%) and 22% fewer overall hospitalized days (95% CI: 16%–28%). Nevertheless, the number of hospitalized days admitted through the emergency room was 10% higher among home care recipients (95% CI: 0%–20%). Conclusions: Volunteer-administered home care might be effective in reducing emergency room visits and non-acute hospitalization, as well as early detection of acute problems warranting tertiary care. Further randomized studies are needed to substantiate this finding.